(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
Special attention is paid to the many meaningful words in linguistics, in particular, the sciences of lexicology and semiology. The appearance of portable meaning in words, that is, the emergence of the state of polysemia and the separation of the people in the process of their application are being approached as the main problems in the study of multi-meaning words. In this article, the role of multi-meaning words in the expression of the national psyche is Free Vahidov she’sstudied in the example of riyati.